Styl dedykacji rękopiśmiennej a czas - Krauz, Maria (Stylistyka, 2021)
The article gives analysis of author’s manuscript dedications inscribed predominantly on the title page. The dedication is a short text, closed in terms of content and composi- tion, in which author ascribes his/her work. The basie pattem of dedicatory formula inclu- des: a name of addressee, a reąuest for reception and a signature of addresser.On one hand dedicatory formulae as the typical minimal texts, serving a polite function of a language, retain continuity and permanence of some of the structures (a few linguistic conventions are repeated); on the other they are distinguished by individual, original mo- difications conceming mainly well thought out and elaborated forms in comparison with minimal pattem.The stylistic form of a dedication depends largely on the relation between addresser and recipient, sociol status of interlocutors, type of relations, the choice of functional style, situation in which the action is performed, the time of formation is less important.Even thought contemporary dedications are characterized by morę straightforward way of addressing recipient, diversity of occasions and spontaneity, they still retain so- lemn naturę of statement.